Cost Control in the United States Postal Service - The Institutional Effects and Implications - Phu, Hung; Dang Thi Viet, Duc (VNU Journal of Science: Policy and Management Studies, 2017)
Nowadays, in times of persisting national budget deficits, issues of corporate finance for state-owned enterprises become a hot topic. This paper explores why the state postal agency/company should rely in outsourcing as a major method to control costs to achieve sustainable financial viability. The paper also explores the link between institution factors and the contracting decisions by using the Value-Institutions-Market (VIM) framework on the federal business data, with a focus on the period of 1995-2007 (where data is available). The overarching question of the study is how the USPS outsourcing decisions were affected by changing business environment. The finding is that at the macro level, contracting is a potential strategy to cut costs for the USPS, as well as for other public agencies and enterprises. However, the degrees the USPS can rely in outsourcing is largely framed by institutions factors, that changes in this category affect the magnitude of contracting. Keywords : #Cost control; #Postal service; #State-Owned Enterprise; #Outsourcing/Contracting-out;